The time traveller book of knights and castles - Hindley, Judy. (London ; Tulsa, OK : Usborne/EDC, 1976)
Captioned illustrations and diagrams describe knights and castles in Europe in the year 1240.
4.0
3-6
3-6
Keywords: Middle Ages -- Juvenile literature; Knights and knighthood -- Juvenile literature; Castles -- Juvenile literature; Middle Ages; Knights and knighthood; Castles; Knights and knighthood; Castles; Middle Ages